Characterization and modeling of soliton transmission at 2.5 gb/s over 200 km - Al-Khateeb, Khalid A. Saeed; Armi, Mohd; Shawal, Mohamad (IIUM Press, 2006)
Soliton characteristics and soliton transmission have been simulated using a VPI simulator. Simulation was also used to construct and study a soliton communication system. Near soliton pulses emitted by an actively mode-locked laser is the compressed in dispersion compensating fiber (DCF) to produce solitons. The effect of non-linearity and active pre-chirping mode-locked laser diode source were also investigated. Assessment on a model system using real data shows that propagation over 250km at 2.5Gb/s in standard fiber with 20ps pulse widths is possible in the 1550nm wavelength range.